Integrated signaling and transcriptome analysis reveals Src family kinase individualities and novel pathways controlled by their constitutive activity - Koutras, Nikolaos; Morfos, Vasileios; Konnaris, Kyriakos; Kouvela, Adamantia; Shaukat, Athanasios-Nasir; Stathopoulos, Constantinos; Stamatopoulou, Vassiliki; Nika, Konstantina (Frontiers in Immunology, 2023)
The Src family kinases (SFKs) Lck and Lyn are crucial for lymphocyte development and function. Albeit tissue-restricted expression patterns the two kinases share common functions; the most pronounced one being the phosphorylation of ITAM motifs in the cytoplasmic tails of antigenic receptors. Lck is predominantly expressed in T lymphocytes; however, it can be ectopically found in B-1 cell subsets and numerous pathologies including acute and chronic B-cell leukemias. The exact impact of Lck on the B-cell signaling apparatus remains enigmatic and is followed by the long-lasting question of mechanisms granting selectivity among SFK members. In this work we sought to investigate the mechanistic basis of ectopic Lck function in B-cells and compare it to events elicited by the predominant B-cell SFK, Lyn. Our results reveal substrate promiscuity displayed by the two SFKs, which however, is buffered by their differential susceptibility toward regulatory mechanisms, revealing a so far unappreciated aspect of SFK member-specific fine-tuning. Furthermore, we show that Lck- and Lyn-generated signals suffice to induce transcriptome alterations, reminiscent of B-cell activation, in the absence of receptor/co-receptor engagement. Finally, our analyses revealed a yet unrecognized role of SFKs in tipping the balance of cellular stress responses, by promoting the onset of ER-phagy, an as yet completely uncharacterized process in B lymphocytes.